Pulmonary rehabilitation outcomes in individuals with chronic obstructive pulmonary disease: a systematic review - Souto-Miranda, Sara (2022)
Background: The magnitude of response to pulmonary rehabilitation (PR) is influenced by the selection of outcomes and measures. Objectives: This systematic review aimed to review all outcomes and measures used in clinical trials of PR for individuals with chronic obstructive pulmonary disease (COPD). Methods: The review involved a search of Scopus, Web of Knowledge, Cochrane Library, EBSCO, Science Direct and PubMed databases for studies of stable individuals with COPD undergoing PR. Frequency of reporting for each domain, outcome and measure was synthesized by using Microsoft Excel. Results: We included 267 studies (43153 individuals with COPD). A broad range of domains (n=22), outcomes (n=163) and measures (n=217) were reported. Several measures were used for the same outcome. The most reported outcomes were exercise capacity (n=218) assessed with the 6-min walk test (n=140), health-related quality of life (n=204) assessed with the Saint George's respiratory questionnaire (n=99), and symptoms (n=158) assessed with the modified Medical Research Council dyspnea scale (n=56). The least reported outcomes were comorbidities, adverse events and knowledge. Conclusions: This systematic review reinforces the need for a core outcome set for PR in individuals with COPD because of high heterogeneity in reported outcomes and measures. Future studies should assess the importance of each outcome for PR involving different stakeholders.